Low-intensity, Kilohertz Frequency Spinal Cord Stimulation Differently Affects Excitatory and Inhibitory Neurons in the Rodent Superficial Dorsal Horn. (21st January 2020) - Lee, Kwan Yeop; Bae, Chilman; Lee, Dongchul; Kagan, Zachary; Bradley, Kerry; Chung, Jin Mo; La, Jun-Ho
Highlights: Low-intensity 10 kHz spinal cord stimulation (SCS) alleviates chronic intractable pain without producing paresthesia. Dorsal horn neurons can be classified into adapting and non-adapting neurons by their response to mechanical stimulation. 10 kHz SCS at intensity below sensory threshold selectively activates non-adapting neurons in vivo. 10 kHz SCS more readily activates GABAergic or tonic-firing neurons than presumed excitatory neurons ex vivo . Abstract: Since 1967, spinal cord stimulation (SCS) has been used to manage chronic intractable pain of the trunk and limbs. Compared to traditional high-intensity, low-frequency (<100 Hz) SCS that is thought to produce paresthesia and pain relief by stimulating large myelinated fibers in the dorsal column (DC), low-intensity, high-frequency (10 kHz) SCS has demonstrated long-term pain relief without generation of paresthesia. To understand this paresthesia-free analgesic mechanism of 10 kHz SCS, we examined whether 10 kHz SCS at intensities below sensory thresholds would modulate spinal dorsal horn (DH) neuronal function in a neuron type-dependent manner. By using in vivo and ex vivo electrophysiological approaches, we found that low-intensity (sub-sensory threshold) 10 kHz SCS, but not 1 kHz or 5 kHz SCS, selectively activates inhibitory interneurons in the spinal DH. This study suggests that low-intensity 10 kHz SCS may inhibit pain sensory processing in the spinal DH by activating inhibitory interneurons without activating DC fibers, resulting in paresthesia-free pain relief.